Preparation and characterization of s-quinolin-2-ylmethyldithiocarbazate functionalized magnetic nanoparticles - Abdul Rahman, Ahmad Jazmi; Miskam, Mazidatulakmam Akmam; How, Fiona Ni Foong (2018)
The Fe3O4 magnetic nanoparticles (MNPs) attached with S-quinolin-2-yl-methyl-dithiocarbazate (SQ2MDTC) have been developed, aiming to function as the heavy metal adsorbent. The surface of MNPs was first coated with (3- aminopropyl)triethoxysilane (APTES) as cross-linker and then SQ2MDTC was covalently incorporated to the coated MNPs. The structural and surface characteristics were investigated by Fourier transform infrared spectroscopy (FT-IR), CHNS elemental analysis, thermogravimetric analysis (TGA), x-ray powder diffraction (XRD), field emission scanning electron microscopy (FESEM), and Brunauer-Emmett-Teller (BET) analysis. The SQ2MDTC functionalized MNPs exhibited high adsorption affinity for aqueous Cu(II) and Pb(II) ions when analysed using inductively coupled plasma optical emission spectrometer (ICP-OES), resulting from complexation of the metal ions by surface amino groups. Findings of the present work highlighted the potential of MNPSQ2MDTC as an effective adsorbent for the removal of heavy metal ions in water and wastewater treatment.